Implementation of Control Principle of Education Management towards Teachers’ Working Performance in Public Secondary Schools in Ilemela Municipality - Mallya, Upendo; Ndomba, Raymond; Mhagama, Michaela (International Journal For Research In Educational Studies, 2023)
This study assessed the implementation of the Control Principle of Educational Management towards teachers' working performance in public secondary schools in Ilemela Municipality, Tanzania. Specifically, the research aimed to propose strategies for improving teachers’ working performance. The study utilized Taylor's Scientific Management Theory and employed a mixed research method approach with a convergent parallel research design. A sample of 104 respondents; that is school heads, teachers, and the District Education Officer, were selected through random and purposive sampling. Data was collected using questionnaires and semi-structured interviews, then analyzed through descriptive statistics using SPSS version 20 and thematic analysis. The findings revealed that the strategies in improving teachers’ working performance include providing training and seminars for heads of schools on school management, providing motivation to teachers, improving and advancing professional development for in-service teachers, ensuring that school heads are committed to their work, and improving the working environment The study emphasized the need for training and seminars for school leaders in school management to enhance the positive impact of the Control Principle in educational management. The study recommends further research in other districts to explore the implementation of other educational management principles and their influence on teacher performance.